Couple of biomimetic surfaces with different morphologies for remanufacturing nonuniform wear rail surface. (1st February 2018) - Sui, Qi; Zhou, Hong; Yang, Lin; Zhang, Haifeng; Feng, Li; Zhang, Peng
Highlights: Nonuniform wear made surface had different wear resistances in different regions. Improvement level of wear resistance increased with the hard layer decreased. Relations between the wear and spacing of units in different regions were studied. Treated surface' wear property in vary regions all followed the area ratio formula. Abstract: In this work, biomimetic laser treatment was performed on repairing and remanufacturing the nonuniform worn rail surface. The wearing depth distribution of three work regions of a failure rail surface was discussed, and different thickness hardening layers with different microstructure, microhardness and wear resistances were detected from the worm surfaces. Varying wear resistances of the surfaces with different biomimetic morphologies were obtained by biomimetic laser treatments, and the corresponding effect on the lubrication sliding wear of treated and untreated surfaces were studied for comparative study. In addition, the relationship between wear resistance and the spacing of units was also provided, which can lay the important theoretical foundation for avoiding the wear resistance of the serious worn surface is less than that of the slight worn surface in the future practical applications.